Effects on coronary heart disease of increasing polyunsaturated fat in place of saturated fat: a systematic review and meta-analysis of randomized controlled trials. - Dariush Mozaffarian (Public Library of Science (PLoS), 2010)
Background Reduced saturated fat (SFA) consumption is recommended to reduce coronary heart disease (CHD), but there is an absence of strong supporting evidence from randomized controlled trials (RCTs) of clinical CHD events and few guidelines focus on any specific replacement nutrient. Additionally, some public health groups recommend lowering or limiting polyunsaturated fat (PUFA) consumption, a major potential replacement for SFA. Methods and findings We systematically investigated and quantified the effects of increased PUFA consumption, as a replacement for SFA, on CHD endpoints in RCTs. RCTs were identified by systematic searches of multiple online databases through June 2009, grey literature sources, hand-searching related articles and citations, and direct contacts with experts to identify potentially unpublished trials. Studies were included if they randomized participants to increased PUFA for at least 1 year without major concomitant interventions, had an appropriate control group, and reported incidence of CHD (myocardial infarction and/or cardiac death). Inclusions/exclusions were adjudicated and data were extracted independently and in duplicate by two investigators and included population characteristics, control and intervention diets, follow-up duration, types of events, risk ratios, and SEs. Pooled effects were calculated using inverse-variance-weighted random effects meta-analysis. From 346 identified abstracts, eight trials met inclusion criteria, totaling 13,614 participants with 1,042 CHD events. Average weighted PUFA consumption was 14.9% energy (range 8.0%-20.7%) in intervention groups versus 5.0% energy (range 4.0%-6.4%) in controls. The overall pooled risk reduction was 19% (RR = 0.81, 95% confidence interval [CI] 0.70-0.95, p = 0.008), corresponding to 10% reduced CHD risk (RR = 0.90, 95% CI = 0.83-0.97) for each 5% energy of increased PUFA, without evidence for statistical heterogeneity (Q-statistic p = 0.13; I(2) = 37%). Meta-regression identified study duration as an independent determinant of risk reduction (p = 0.017), with studies of longer duration showing greater benefits. Conclusions These findings provide evidence that consuming PUFA in place of SFA reduces CHD events in RCTs. This suggests that rather than trying to lower PUFA consumption, a shift toward greater population PUFA consumption in place of SFA would significantly reduce rates of CHD. Please see later in the article for the Editors' Summary.